Analisis Capaian dan Hambatan Dalam Penerapan Knowledge Management SECI Pada Yayasan Rumah Kreatif dan Pintar Kota Banjarmasin - Hetty Hyvia Widiyanti; Tomi Oktavianor (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
This research intends to prove and analyze the achievements and obstacles in the implementation of knowledge management SECI studies on the Foundations of a House Creative and Smart. The research method used is descriptive qualitative data collected in the form of words, images, and not the numbers of data, from this opinion described the descriptive study to obtain data may be derived from manuscripts, interviews, field notes, photos, video recordings, private documents, notes or memos, and other official documents. The technique of determination of informants in this study uses purposive sampling andsnowball sampling. The results of the study found that the Implementation of the Conversion SECI will be optimal if it is supported by four supporting components, namely Knowledge, infrastructure / Facilities Support available, psychological, level of solidarity trust against members of the target, and tangible assets. If the supporting component is not owned, then the implementation of the Conversion SECI relative can still be done, just that it has the limitation and its purpose is not optimal. Based on the discussion and findings above that in the application of knowledge management conversion SECI it is inseparable from the fourth process (Socialization, Externalization, Combination, and Internalization) everything was interrelated and continuous so that the achievement of a Foundation HouseCreative and Smart could be more effective. But in reality, that occurs the Foundation of the House Creative and Smart has the biggest obstacle during the process of combination because of the limitation of Knowledge in it. So, the next step of Internalization has not been able to effectively. But the overall inhibition of one process and have not being able to optimally continue the implementation of the next stage does not close the possibilityof the Foundation of the House Creative and Smart not able to implement the Conversion of SECI just still less effective.Keywords: Achievements, Barriers, Implementation of Knowledge Management Conversion SECI, Socialization, Externalization, Combination, Internalization.